Endovascular Treatment of Anterior Circulation Large Vessel Occlusion in the Elderly - Jayaraman, Mahesh V.; McTaggart, Ryan A. (Frontiers in Neurology, 2018)
Abstract Endovascular treatment of anterior circulation large vessel occlusion in the elderly population presents special challenges and opportunities. In this review, we discuss the published literature regarding thrombectomy in elderly patients, and also discuss specific issues related to treatment in this patient population. In summary, while the overall outcomes following thrombectomy in elderly patients are worse than following thrombectomy in younger patients, there appears to be a similar benefit as in young patients. While there are challenges with successfully delivering thrombectomy in older patients, age alone should not be an independent exclusion from thrombectomy.